Antioxidant and antihyperglycemic activities of Scorzonera cinerea radical leaves in streptozocin-induced diabetic rats - Temiz Mehmet Ali (Acta Pharmaceutica)
Scorzonera species are used for treating various diseases. They are consumed raw, especially in the spring, and have nutritious and dietetic values. This study evaluated the antidiabetic and antioxidant effects of ethanolic extracts of Scorzonera cinerea (Sc) radical leaves in diabetes mellitus. Five random groups of Wistar rats (n = 8) were created – control, diabetic, acarbose, Sc-Dried, and Sc-Frozen. Phenolic profiles of extracts were determined by HPLC. Free radical scavenging capacity was measured using DPPH and ABTS tests. The inhibitory effects of Sc extracts on α-glucosidase and α-amylase activities were also evaluated. Moreover, superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) activities, glutathione (GSH) concentration, malondialdehyde (MDA), total antioxidant status (TAS) and total oxidant status (TOS) were analyzed in the liver tissues. While dried Scorzonera extract was more effective in α-amylase inhibitory activity, frozen Scorzonera extract was more effective in α-glucosidase inhibitory activity. Sc-Dried and Sc-Frozen extracts lowered blood glucose and HbA1c levels, they also increased insulin. Although liver MDA and TOS were significantly increased in the diabetic group, their values were significantly lower in the Sc-Dried- and Sc-Frozen-treated groups. GSH, TAS, and anti-oxidant enzyme activities decreased in the diabetic group, but Sc-Dried and Sc-Frozen supplements significantly enhanced liver antioxidant values. In conclusion, S. cinerea treatment exerts potential hypoglycemic and antioxidant effects in diabetes. Thus, it can be considered as a candidate dietary supplement for health benefits in diabetes.